Health Problems Among Workers Who Recycle Electronic Waste in Southern Thailand - Somsiri Decharat (Osong Public Health and Research Perspectives, 2020)
Objectives This study evaluated the prevalence of adverse health effects among recycling facility workers, and described their socioeconomic situation, health symptoms and work characteristics. Methods A cross-sectional study was conducted by interviewing 71 workers in 20 electronic waste (e-waste) recycling facilities in southern Thailand. Data were collected by questionnaire. Risk factors were evaluated using multiple logistic regression analysis. Results Recycling facility workers with blurred vision were significantly associated with being male (p = 0.035), over 40 years old (p = 0.020), and having ≤ secondary school education (p = 0.017). Rash/itching was associated with being male (p = 0.011), over 40 years (p = 0.018), having ≤ secondary school education (p = 0.012). not using a cloth mask (p = 0.019), not using gloves (p = 0.028), not washing hands before lunch (p = 0.005), not cleaning clothes daily (p = 0.025), and not having established ventilation systems in the place of work (p = 0.018). Hand-and-feet numbness were associated with being male (p = 0.025), and being over 40 years (p = 0.023). Headaches were associated with being male (p = 0.028). Conclusion Personal hygiene is important for this occupational group, and it should be emphasized in education programs.